Integratiton of GIS (Geographic Information System) and locative tools in pedagogical and ludic practices for museums - Perales Blanco, Verónica; Adam, Fred (Arte, Individuo y Sociedad, 2013)
The goal of this article is to make, at first, an analysis of some pedagogical and/or ludic practices held in museums -nationally or internationally- involving the use of geo-referencing or locative tools in its development. The integration of new technologies to support research and cultural diffusion is essential. The benefits are evident, from the improvement of knowledge and conservation of artworks, to the seduction of a young population sector that links, most of times, using technologies to discover and global experience.Then describe some proposals raised in the context of Conocimiento Aumentado y Accesibilidad: la Representación Museográfica de Contenidos Culturales Complejos research project funded by the Education and Science Ministry in Spain.
Keywords: GIS; pedagogy; ludic; visualization; geolocation; geocaching; QR code; museum